Assessing Reliability and Validity of an Instrument for Measuring Resilience Safety Culture in Sociotechnical Systems - Gholamabbas Shirali; Mohammad Shekari; Kambiz Ahmadi Angali (Elsevier, 2018)
Background: Safety culture, acting as the oil necessary in an efficient safety management system, has its own weaknesses in the current conceptualization and utilization in practice. As a new approach, resilience safety culture (RSC) has been proposed to reduce these weaknesses and improve safety culture; however, it requires a valid and reliable instrument to be measured. This study aimed at evaluating the reliability and validity of such an instrument in measuring the RSC in sociotechnical systems. Methods: The researchers designed an instrument based on resilience engineering principles and safety culture as the first instrument to measure the RSC. The RSC instrument was distributed among 354 staff members from 12 units of an anonymous petrochemical plant through hand delivery. Content validity, confirmatory, and exploratory factor analysis were used to examine the construct validity, and Cronbach alpha and test-retest were employed to examine the reliability of the instrument. Results: The results of the content validity index and content validity ratio were calculated as 0.97 and 0.83, respectively. The explanatory factor analysis showed 14 factors with 68.29% total variance and 0.88 Kaiser-Meyer-Olkin index. The results were also confirmed with confirmatory factor analysis (relative Chi-square = 2453.49, Root Mean Square Error of Approximation = 0.04). The reliability of the RSC instrument, as measured by internal consistency, was found to be satisfactory (Cronbach α = 0.94). The results of test-retest reliability was r = 0.85, p < 0.001. Conclusion: The results of the study suggest that the measure shows acceptable validity and reliability. Keywords: Instrument, Reliability, Resilience safety culture, Validity